An Exploration of Interpersonal Communication Patterns in Agape Fellowship Centre at Madaraka Estate Nairobi - Murimi, J. B. K. (Daystar University, School of Communication, 1999)
The purpose of the study was to explore interpersonal communication patterns in Agape Fellowship Centre (AFC) at Madaraka Estate, Nairobi. A descriptive survey method was used and a self-administered questionnaire was distributed to a sample of 110 members of AFC. However, 99 questionnaires formed the basis of data after editing. This study established that despite the depth of Christian values, members of the same congregation get their interpersonal needs met through selective interpersonal communication/ relationships. This selectivity, referred to as interpersonal communication choice, the study estab- lished, is influenced in diverse degrees by various factors which include age group, gender, social/ economic status, education level, proximity and friendship, with the area of residence having the highest influence. The study revealed that the majority of the members of AFC congregation appre- ciated, and indeed, interacted with other members, allaying the fears the researcher had and which prompted this study. However there were some members of the congregation who did not visit other members while some others were not visited at all. While the pastor was depicted to be people-centred, he was, however, por- trayed by the data to attend to physical needs of members a little bit more than their spiritual needs. While recommendations on the line of action by the pastor and the leadership team have been suggested to help AFC in arresting the negative rate of growth detected and instead attain even a higher level of growth, further study, using this survey as the basis, has been recommended to establish the impact, if any, of interpersonal communication on church growth.
Thesis
Keywords: interpersonal communication patterns; Christian values